Eduecolinguistic Learning Design in Indonesian Formal Educational Institutions: An Islamic Perspective - Nugraha, Tubagus Chaeru; Tarshany, Yasser M A Rahman; Suherman, Agus M A Rahman; Amalia, Rosaria M; Uray, Uray M (Islamic Research, 2025)
Environmental problems in the world in general and in Indonesia in particular currently require serious solutions to create a conducive environment for future generations. This research describes education about environmental issues and the importance of ecological awareness in the younger generation. The research method used is descriptive quantitative which aims to analyse the environmental awareness of students and university students on the importance of protecting the environment. There are three stages of research, namely: data provision, data analysis, and data presentation—the first stage, providing data using a questionnaire with an online questionnaire instrument, namely Google Form. As for the research sample, namely junior high school students, high school students, university students, 350 respondents were selected using simple random sampling technique. The second stage is data analysis with content analysis and data verification from local environmental experts. In the third stage, the data is presented in the form of tables and graphs. The results showed that the positive response of students and college students towards environmental awareness was very good 80%. Awareness of the need to actively participate in building public awareness of the importance of protecting the environment, the percentage of positive responses is very good 97.77%. The students also understand that there are environmental problems in West Java, the most important of which is the problem of waste and water pollution and provide plans for various social actions to provide solutions to these problems, such as socialising the importance of (3R) reduce, reuse, and recycle; Other activities, such as: Donating used items that are still good, planting plants, and limiting the use of water and electricity.